Disabled Children's Childhood Studies
XVI, 204 p.
Keywords: This collection offers first-hand accounts, research studies and in-depth theoretical explorations of disabled children's childhoods. The accounts oppose the global imposition of problematic views of disability and childhood and instead, offer an open discussion of responsive and ethical research approaches.